MEDIA OF LITERARY WORKS AND SYMBOLIC SOCIAL MOVEMENTS OF MAS MARCO KARTODIKROMO - Sulton, Agus (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2022)
This study aims to identify and discover the ideas of social change offered by Mas Marco Kartodikromo through his work. Mas Marco Kartodikromo is an active person who writes literary works and articles in the early 20th century. The results of his writings present ideas for social change and the theme of the injustice of the system applied by the Dutch colonial government. The results of this study indicate that the idea of social change offered by Mas Marco Kartodikromo concerns the issue of nationalism for the Indies homeland, the idea of independence for the Indies homeland, defending the rights of indigenous women in the Indies, and improving the policy system in the Indies. Broadly speaking, the narratives written by Mas Marco Kartodikromo provide awareness to the readers so that the Indies quickly get out of the Dutch colonial shackles to become an independent state.